Improved Ferroelectric and Leakage Properties of Ce Doped in BiFeO3 Thin Films. (5th June 2014) - Bai, Alima; Zhao, Shifeng; Chen, Jieyu
Abstract : Ce doped BiFeO3 thin films with a perovskite structure were prepared using solution-gelation method. It shows that the ferroelectric properties have been enhanced after doping Ce. The enhanced ferroelectric properties are attributed to the structural transformation and the reduced leakage current after doping rare metal of Ce. It has been found that the phase structures of the films transfer from rhombohedral symmetry structure to the coexistence of the tetragonal and orthorhombic symmetry structure. And Fe 2+ ions have been reduced, which leads to the decreased leakage for Ce doped BiFeO3 thin films. The present work can provide an available way to improve the ferroelectric and leakage properties for multiferroic BiFeO3 based thin films.